1999
DOI: 10.1246/cl.1999.37
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure of J Aggregates of Pseudoisocyanine Chloride Dyes at a Mica/Solution Interface Revealed by AFM

Abstract: By using tapping-mode atomic force microscopy (AFM), we revealed for the first time the structure of J aggregates of pseudoisocyanine chloride(PIC-Cl) dyes at a mica/solution interface in an aqueous PIC-Cl solution. The J aggregates were leaf-like islands in multilayers of PIC-Cl molecules. The minimal size of the aggregate necessary for the J band was also revealed. Dye molecules grow into the J aggregates at a mica/solution interface by a Volmer-Weber type growth process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…In previous studies, we solved this difficulty by using tapping mode atomic force microscopy (TM-AFM) and revealed for the first time the real structure of the J aggregate of PIC-Cl at a mica/liquid interface in an aqueous PIC-Cl solution. 16,17 Contrary to previously accepted models in which J aggregates at a mica/solution interface have two-dimensional monolayer structures, 7,8 our AFM images showed that the aggregates have three-dimensional leaf-like island structures. Furthermore, the morphological change revealed by AFM imaging suggests that the J aggregates grow by a Volmer-Weber type growth process.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we solved this difficulty by using tapping mode atomic force microscopy (TM-AFM) and revealed for the first time the real structure of the J aggregate of PIC-Cl at a mica/liquid interface in an aqueous PIC-Cl solution. 16,17 Contrary to previously accepted models in which J aggregates at a mica/solution interface have two-dimensional monolayer structures, 7,8 our AFM images showed that the aggregates have three-dimensional leaf-like island structures. Furthermore, the morphological change revealed by AFM imaging suggests that the J aggregates grow by a Volmer-Weber type growth process.…”
Section: Introductioncontrasting
confidence: 99%
“…Previous reports state that PIC−Cl forms J aggregates at a mica/solution interface when the concentration of PIC−Cl exceeds 1.0 × 10 -4 M. , We examined the growth process of these J aggregates in detail. Figure shows typical absorption spectra of aqueous PIC−Cl solutions . The spectra showed quasi-adsorption behavior (Figure , inset).…”
Section: Resultsmentioning
confidence: 99%
“…The specific structures of the J -aggregates are typical of a head-to-tail intermolecular association between the molecular units [2]. Formation of the J -aggregates of PIC has been reported for various types of reaction systems, e.g., solutions [2,3] and interfaces [4]. Preference for the PIC cations to form J -aggregates rather than the generally more common H -aggregates is mainly due to the molecular structure of PIC (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…We will discuss the growth processes of the mesoscopic aggregates based on in situ AFM measurements. [67][68][69] 4.1 Three-dimensional mesoscopic morphology of pseudoisocyanine J-aggregates at a mica/solution interface Fig. 21(a) shows an optical path length dependence on the absorption spectrum of an aqueous PIC solution (2.0 mM) in a custom-made cell.…”
Section: Morphology Transformation Of Interfacial J-aggregates Involv...mentioning
confidence: 99%